2018
DOI: 10.1093/annonc/mdy264
|View full text |Cite
|
Sign up to set email alerts
|

Phase III, randomised trial of avelumab versus physician’s choice of chemotherapy as third-line treatment of patients with advanced gastric or gastro-oesophageal junction cancer: primary analysis of JAVELIN Gastric 300

Abstract: BackgroundThere currently are no internationally recognised treatment guidelines for patients with advanced gastric cancer/gastro-oesophageal junction cancer (GC/GEJC) in whom two prior lines of therapy have failed. The randomised, phase III JAVELIN Gastric 300 trial compared avelumab versus physician’s choice of chemotherapy as third-line therapy in patients with advanced GC/GEJC.Patients and methodsPatients with unresectable, recurrent, locally advanced, or metastatic GC/GEJC were recruited at 147 sites glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
370
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(389 citation statements)
references
References 22 publications
11
370
1
7
Order By: Relevance
“…Currently, evidence for standard-of-care in third-or later-line therapy for patients with advanced G/GEJ cancer is limited. This includes studies such as KEYNOTE-059 [10], INTEGRATE [11], TAGS [12], JAVELIN Gastric 300 [13], and a Chinese apatinib study [14]. Most of the studies do not provide evidence of long-term efficacy in patients with G/GEJ cancer, with the exception of the phase 2 KEY-NOTE-059 study that evaluated the long-term efficacy and safety of pembrolizumab, another immune checkpoint inhibitor [15].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, evidence for standard-of-care in third-or later-line therapy for patients with advanced G/GEJ cancer is limited. This includes studies such as KEYNOTE-059 [10], INTEGRATE [11], TAGS [12], JAVELIN Gastric 300 [13], and a Chinese apatinib study [14]. Most of the studies do not provide evidence of long-term efficacy in patients with G/GEJ cancer, with the exception of the phase 2 KEY-NOTE-059 study that evaluated the long-term efficacy and safety of pembrolizumab, another immune checkpoint inhibitor [15].…”
Section: Introductionmentioning
confidence: 99%
“…The JAVELIN 300 study evaluated avelumab versus physician's-choice paclitaxel or irinotecan in patients who had received ≥2 lines of chemotherapy. 67 Avelumab did not improve OS versus chemotherapy, and no benefit was seen in a subgroup analysis of PD-L1-positive patients (≥1% of tumor cells). Finally, preliminary results of the phase 3 KEYNOTE-181 study evaluating second-line pembrolizumab versus physician's-choice docetaxel or irinotecan in patients with advanced esophageal/GEJ carcinoma (64% SCC) show that pembrolizumab significantly improved RR, median OS (9.3 vs 6.7 months; HR, 0.69; P = .0074), and 12-month OS (43% vs 20%) in patients whose tumors expressed PD-L1 CPS ≥10 (n = 222).…”
Section: Third-line Setting and Beyondmentioning
confidence: 91%
“…Furthermore, patients with GEJ tumors also appeared to benefit (HR, 0.61), whereas patients with gastric tumors did not. The JAVELIN 300 study evaluated avelumab versus physician’s‐choice paclitaxel or irinotecan in patients who had received ≥2 lines of chemotherapy . Avelumab did not improve OS versus chemotherapy, and no benefit was seen in a subgroup analysis of PD‐L1–positive patients (≥1% of tumor cells).…”
Section: Treatment Of Metastatic Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…Positive results have been obtained only for anti-HER2 agent, trastuzumab, in HER2 positive GC, which may be used as first-line treatment, and for an anti-angiogenic agent, ramucirumab, which may be used in the second line of treatment, and for which no predictive factors of response have been identified [70][71][72]. The recent interest in the potential efficacy of immune check points inhibitors brought some hope, with some positive phase II and III studies [73,74], but not confirmed by other studies [75,76]. The future challenge will be to use all the available histological and molecular markers to identify the patients susceptible to benefit from specific treatments.…”
Section: Treatment Of Advanced Gcmentioning
confidence: 99%